IMF Staff papers : Volume 32 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1985)
This paper describes that publications of the IMF are one way in which this responsibility is discharged. Through the publication of Staff Papers, the IMF is making available some of the work of members of its staff. The IMF believes that these papers will be found helpful by government officials, by professional economists, and by others concerned with monetary and financial problems. On some international monetary problems, final and definitive views are scarcely to be expected in the near future, and several alternative, or even conflicting, approaches may profitably be explored. The views presented in these papers are not, therefore, to be interpreted as necessarily indicating the position of the Executive Board or of the officials of the IMF. The selected references presented in this bibliography cover books, pamphlets, reports, and periodical articles that describe the functions, organization, and activities of the IMF. Publications on the various aspects of international economics are included only when they contain material relating specifically to the IMF.